Arthur$1 (Bs TV troubles - Brown, Marc Tolon (Boston : Little, Brown, 1995)
When Arthur sees advertisements for the amazing doggy Treat Timer, he decides to earn enough money to buy it for his dog Pal.
"An Arthur adventure"--Cover.
Keywords: Advertising -- Fiction; Moneymaking projects -- Fiction; Brothers and sisters -- Fiction; Aardvark -- Fiction